1994
DOI: 10.1530/eje.0.1300446
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between calcitrophic hormones and blood pressure in elderly subjects

Abstract: The relationship between calcitrophic hormones and blood pressure has been investigated in 583 elderly subjects who were untreated for hypertension. Univariate analysis demonstrated that serum parathyroid hormone, calcitriol, albumin and calcium were correlated significantly with mean blood pressure (r = +0.15, +0.10, +0.14 and +0.11, respectively), as were body mass index and age (r = +0.19 and +0.10, respectively). Parathyroid hormone also was correlated positively with both age and calcitriol (r = +0.34 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 7 publications
3
19
0
Order By: Relevance
“…In a group of 583 elderly patients untreated for hypertension and who did not suffer from primary HPT, calcium and PTH levels significantly correlated with mean BP, and PTH correlated positively with age (16). Similar results were obtained in patients with essential hypertension, confirming the presence of alteration of calcium metabolism in those patients (20).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In a group of 583 elderly patients untreated for hypertension and who did not suffer from primary HPT, calcium and PTH levels significantly correlated with mean BP, and PTH correlated positively with age (16). Similar results were obtained in patients with essential hypertension, confirming the presence of alteration of calcium metabolism in those patients (20).…”
Section: Discussionsupporting
confidence: 69%
“…In fact, calciotropic hormones, such as PTH and calcitriol, have been shown to be increased in some forms of hypertension. St John et al (16), in a group of hypertensive elderly subjects, showed that PTH was an independent significant predictor of mean BP. Moreover, PTH levels, which are elevated both in patients with HPT and in those with essential hypertension, can probably influence intracellular calcium levels and subsequently smooth muscle contraction (17).…”
Section: Discussionmentioning
confidence: 96%
“…A modest J-or U-shaped association was found (P value for quadratic PTH ϭ 0.08). Results were not materially changed after including 25 Among the components, a significant inverse multivariate association of 25(OH)D with fasting hyperglycemia in men and a positive association with high triglycerides in women were present (P trend ϭ 0.01 for both) ( Table 3). The adjusted odds of high blood pressure, hyperglycemia, and low HDL were significantly elevated among men in the highest quintile of PTH compared with men in the lowest quintile.…”
Section: Discussionmentioning
confidence: 94%
“…Elevated PTH secondary to low vitamin D increases calcium resorption from the skeleton at the expense of an increased risk of fracture (20). Secondary hyperparathyroidism may also increase the risk of developing components of metabolic syndrome, including hypertension (21)(22)(23)(24)(25)(26), obesity (6,9,10,(27)(28)(29), and diabetes (30 -32). However, we are unaware of previous research investigating whether PTH levels are also associated with the metabolic syndrome.…”
mentioning
confidence: 99%
“…St. John et al (27) investigated the relationship between calcitropic hormones and blood pressure in 583 elderly subjects who were untreated for hypertension, but who were not vitamin D deficient. Univariate analysis demonstrated that serum PTH and 1,25-(OH) 2 D 3 were correlated significantly with mean blood pressure.…”
Section: Discussionmentioning
confidence: 99%